Investigation of phosphatases in Ascaridia galli, A Bird Nematode parasite - R. D. Barde, Govind H. Balde* (Recent Research in Science and Technology, 2011)
<span style="font-size: 10pt; font-family: ";Arial Narrow";,";sans-serif";; mso-fareast-font-family: 'Times New Roman'; mso-ansi-language: EN-US; mso-fareast-language: EN-US; mso-bidi-language: AR-SA; mso-bidi-font-family: 'Times New Roman';">Phosphates play an important role in metabolic activities especially in carbohydrate metabolism. The phosphatases constitute a large group of enzymes that are involved in many important phases of intermediary metabolism. They are differentiated into three types i.e. A) pyrophosphatases (inorganic and organic) B) phosphomonoesterases C) phosphodiesterases. Depending upon the substrates that are singly or doubly esterified phosphatates to which these are specific, respectively. These group, in turn, has two sub groups one of low and the other of high specificity. The phosphomonoesterases of low specificity will have optimum activity either in the acid or alkaline range, depending upon which these can be acid or alkaline phosphatases which is recovered from Ascaridia galli SchrankÃ‚Â  [5] from Nanded region (M.S.) India.